Peran Kinerja Lingkungan dalam Memediasi Pengaruh Green Organizational Culture terhadap Organizational Citizenship Behavior - Sofyan Hamid; Shandra Bahasoan; Nurul Fitrah (Al-Buhuts, 2025)
This study aims to analyze the effect of Green Organizational Culture on Organizational Citizenship Behavior with environmental performance as a mediating variable. This study uses a quantitative approach with a survey method of employees at PT PLN (Persero) UIW Sulselrabar. Data were analyzed using SEM-PLS to test the causal relationship between variables. The results show that Green Organizational Culture has a positive and significant effect on environmental performance and Organizational Citizenship Behavior. In addition, environmental performance was found to significantly mediate the relationship between Green Organizational Culture and Organizational Citizenship Behavior. These findings confirm that strengthening a sustainability-based organizational culture not only improves environmental performance but also encourages voluntary employee behavior that supports organizational effectiveness. This study provides empirical contributions to the development of green management and organizational behavior literature, particularly in the context of organizations in Indonesia.